Degradation of biogas in a simulated landfill cover soil at laboratory scale: Compositional changes of main components and volatile organic compounds. (15th February 2023) - Randazzo, Antonio; Zorzi, Francesca; Venturi, Stefania; Bicocchi, Gabriele; Viti, Gregorio; Tatàno, Fabio; Tassi, Franco
Graphical abstract: Highlights: An experimental setup (digester + soil column) was developed to simulate landfills. Main gaseous components, VOCs, and 13 C/ 12 C ratios in CO2 and CH4 were monitored. CH4 and H2 were degraded during the permeation along the cover soil. Benzene and short-chain alkane contents increased along the cover soil. Odorous terpenes and oxygenated compounds were recalcitrant at oxidising conditions. Abstract: A laboratory experiment lasting 28 days was run to simulate a typical landfill system and to investigate the compositional changes affecting the main components (CH4, CO2, and H2 ) and nonmethane volatile organic compounds from biogas generated by anaerobic digestion of food waste and passing through a soil column. Gas samples were periodically collected from both the digester headspace and the soil column at increasing distances from the biogas source. CH4 and H2 were efficiently degraded along the soil column. The isotopic values of δ 13 C measured in CH4 and CO2 from the soil column were relatively enriched in 13 C compared to the biogas. Aromatics and alkanes were the most abundant groups in the biogas samples. Among these compounds, alkylated benzenes and long-chain C3+ alkanes were significantly degraded within the soil column, whereas benzene and short-chain alkanes were recalcitrant. Terpene and O-substituted compounds were relatively stable under oxidising conditions. Cyclic, alkene, S-substituted, and halogenated compounds, which exhibited minor amounts in the digester headspace, were virtually absent in the soil column. These results pointed out how many recalcitrant potentially toxic and polluting compounds tend to be relatively enriched along the soil column, claiming action to minimise diffuse landfill gas (LFG) emissions. The proposed experimental approach represents a reliable tool for investigating the attenuation capacities of landfill cover soils for LFG components and developing optimised covers by adopting proper soil treatments and operating conditions to improve their degradation efficiencies.